Español Competences in information and communication technology of the nursing professional in institutions of the first level of care Chiclayo, 2020 - Alamo Valdera, Erika (2022)
Objective: To determine the competences in information and communication technology of the nursing professional in institutions of the first level of care Chiclayo, 2020. Method: Pilot study of a quantitative type, non-experimental, descriptive cross-sectional design. The population and sample consisted of 25 nursing professionals who work in primary care at the José Olaya, José Leonardo Ortiz Health Centers and the Túpac Amaru health post; the sampling was non - probabilistic for convenience. The instrument used was the questionnaire entitled " Knowledge, Skills and Attitudes in the use of Internet and New Technologies in the nursing professional"; it complies with the premises of reliability and validity, its reliability being 0.893 according to the Cronbach Alpha. The data were analyzed by means of descriptive analysis of variables, measures of central tendency were found and presented in graphs with the help of SPSS version 25 software. During the research, the criteria of scientific rigor and the principles of ethical rigor were considered. Main results:  Nursing professionals have basic knowledge (56%), basic skills (100%) and favorable attitudes (92%) towards ICT. Overall conclusion: Nursing professionals of the first level of care still do not have Technological competencies of information and communication; due to the fact that knowledge and skills towards ICT are basic and only attitudes are favorable, this represents a value of (2.0), value below the expected mean (3.0).